Designing for change: design solutions for anthropogenic and climate change impacts on riparian ecosystems and hydrology in Northeast Kansas - Akers, Ashley (Kansas State University, 2021)
Anthropogenic climate change has been recognized as a threat to rivers and their riparian corridor. Climactic conditions influenced by anthropogenic activity such as temperature increase, extended drought periods, large precipitation events, and water shortages are projected to rapidly increase within the next century. This project addresses some of the negative effects of anthropogenic climate change on the Kansas River. These effects include channel function, floodplain disconnection from the river, and riparian ecosystem fragmentation (fragmentation of native riparian habitats, both freshwater and terrestrial species). This project approaches riparian vegetation and floodplain restoration through the use of the existing physical integrity of the river channel and floodplain as a template to reconnect the Kansas and Wakarusa Rivers to their geomorphic floodplain, in conjunction with expansion of the native riparian vegetation buffers. Native riparian vegetation and floodplain restoration implementation and management strategies were assessed in case studies and projected onto four study sites in this project: three on the Kansas River, and one on the Wakarusa River (a tributary of the Kansas River). The purpose of this project is to provide examples of native riparian vegetation and floodplain restoration application within the context of landscape architecture in Kansas at sites with varying existing site conditions and needs.
Keywords: Riparian restoration; Floodplain restoration; Landscape architecture